Why Are Some Snakes More Terrifying and What Is Behind the Fear? - Frynta, Daniel; Janovcová, Markéta; Elmi, Hassan Sh Abdirahman; Štolhoferová, Iveta; Rudolfová, Veronika; Rexová, Kateřina; Sommer, David; Král, David; Berti, Daniel Alex; Landová, Eva; Frýdlová, Petra (Animals, 2025)
Snakes are stimuli inducing an ancestral fear response in humans and other primates. Certain snakes evoke more subjective fear than others. True vipers are high-fear-eliciting snakes for both African and European respondents. This can be explained by the evolutionary experience of human ancestors in Africa. The question arises as to how snakes living in the Americas and Australia, with which humans have no evolutionary experience, will be evaluated. While these snakes belong to broader taxonomic groups that have distant relatives in the Old World, they have evolved independently for tens of millions of years. We prepared a set of 32 pictures depicting eight American pit vipers, eight Australian elapids, eight constrictors, and eight colubrids and asked the respondents to rank these stimuli according to the fear these snakes evoke. Here, we show a high cross-cultural agreement between evaluations by African and European respondents. Snakes characterized by a robust body shape, such as American pit vipers, Australian death adders, pythons, and boas, were the most fear-evoking. The body width was the strongest predictor of evoked fear. The contribution of coloration and pattern of the stimulus to the fear response was not proved. This supports the view that the patterns of fear are not dependent on direct experience, but its underlying mechanisms are shared cross-culturally.
Keywords: Elapidae; cross-cultural comparison; ophidiophobia; Viperidae; fear; Boidae; evolutionary psychology